Uso de redes sociales en el rendimiento académico de los estudiantes universitarios - Beltrán Rey, Thalia Mari Gette (2025)
Social media are virtual platforms that allow individuals to interact and exchange content in real-time and from anywhere in the world. Over the past few years, especially post-pandemic, they have also become an essential tool in educational practices. Acquiring relevance and having either a positive or negative influence on academic performance. This research aimed to determine the impact of social media use on the academic performance of university students, identifying the effects of its use and establishing the factors that contribute to improving academic performance. The study was conducted using a nonexperimental qualitative approach, with a cross-sectional design, and a correlational and descriptive scope; the sample consisted of 14 scientific articles in which 2,480,308 individuals were studied. The analysis revealed that the impact of social media can affect academic performance both positively and negatively; on one hand, they contribute to organization and collaborative work, but excessive use can cause distraction and delays in various tasks. Furthermore, various factors were identified that contribute to improving academic performance, including the family environment, available educational resources, access to technology, teaching methodology, and the psychosocial conditions of the student. Additionally, proper time management, family and teacher support, and a balance between study and work are essential for optimizing learning and achieving efficient academic performance, allowing students to successfully face academic challenges